The Influence of Profitability, Dividend Policy, and Debt Policy on Firm Value in State-Owned Banks Listed on the Indonesia Stock Exchange for the Period 2014-2023 - Sofia Muninggarsih; Eko Giyartiningrum (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study is expected to provide a clear picture of factors influencing firm value such as profitability, dividend policy, and debt policy in State-Owned Enterprises (BUMN) companies in the banking sector listed on the Indonesia Stock Exchange (IDX) in 2014-2023. This study examines the effect of profitability, dividend policy, and debt policy on firm value. Data analysis used in the study included descriptive statistics, classical assumption tests, multiple regression analysis, and hypothesis testing. The significance level used in the research is 5%. The study results are that profitability and dividend policy have a significant effect on firm value, while debt policy does not affect firm value. Profitability, dividend policy, and debt policy together affect firm value.